2015
DOI: 10.1016/j.ijpharm.2015.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Reversible hydrophobic ion-paring complex strategy to minimize acylation of octreotide during long-term delivery from PLGA microparticles

Abstract: Acylation of peptide has been reported for a number of peptides and proteins during release from polymers comprising of lactide and glycolide. We hypothesize that reversible hydrophobic ion-pairing (HIP) complex may minimize octreotide acylation during release. Sodium dodecyl sulfate (SDS), dextran sulfate A (DSA, Mw 9–20kDa) and dextran sulfate B (DSB, Mw 36–50kDa) were selected as ion-pairing agents to prepare reversible HIP complex with octreotide. Complexation efficiency was optimized with respect to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Other examples of HIP complexation include heparin with deoxycholylethylamine [348] and insulin with PC [351]. HIP was also used as a strategy to prevent acylation of octreotide during release from microparticles composed of lactide and glycolide [352]. there is considerable debate on how they alter intestinal permeability.…”
Section: Peptide Hydrophobisationmentioning
confidence: 99%
“…Other examples of HIP complexation include heparin with deoxycholylethylamine [348] and insulin with PC [351]. HIP was also used as a strategy to prevent acylation of octreotide during release from microparticles composed of lactide and glycolide [352]. there is considerable debate on how they alter intestinal permeability.…”
Section: Peptide Hydrophobisationmentioning
confidence: 99%
“…We have previously shown that acylation of octreotide from PGLA MPs-in-gel system can be minimized by using hydrophobic ion-pairing approach (Vaishya et al, 2015b). However, release rate was very high and as a result >80% octreotide was released within 3 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Reversible hydrophobic ion pairing (HIP) complex strategy was used to minimize octreotide acylation during long time delivery from PLGA microparticles by Vaishya et al Sodium dodecyl sulfate and dextran sulfate with different molecular weights were used as ion pairing agents to prepare HIP complex with octreotide [21]. Microparticles were prepared with HIP complexed with octreotide and PLGA polymer.…”
Section: Novel Colloidal Delivery Systemsmentioning
confidence: 99%
“…Octreotide was released for extended time period. A large percentage of released octreotide was in native form and only less than 7% was acylated [21]. In addition, Shirangi et al inhibited acylation by temporarily and reversibly block the amine groups in the peptide chain with a protective group.…”
Section: Novel Colloidal Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation